The Influence of Leadership, Motivation and Work Environment on Employee Performance at the Regional Inspectorate of Kaur Regency - Putri Madalena; Eska Prima Monique Damarsiwi; Abdul Rahman (Journal of Indonesian Management, 2021)
The purpose of this study is to determine the influence of leadership, motivation and work environment on employee performance at the Regional Inspectorate of Kaur Regency. The sample in this study was 31 civil servants at the Regional Inspectorate of Kaur Regency. The data collection used a questionnaire and the analytical methods used were multiple linear regression, determination test and hypothesis testing. The multiple regression results show the equation Y = 0.678+0.287X1+0.373 X2+0.354X3, The result of regression direction is positive so it means that the variables of leadership, motivation and work environment will also increase. The value of the coefficient of determination is 0.640. This means that X1 (leadership), X2 (motivation), X3 (work environment) has a contribution to performance (Y) of 64% while the remaining 36% is influenced by other variables not examined in this study. Overall, the results of the t test have a significant value less than 0.05, so it can be interpreted that X1 (leadership), X2 (motivation), X3 (work environment) have a significant influence on performance (Y) partially or individually. The results of the F test have a significance value of 0.000 < 0.05. Because the significance level below 0.05 indicates that together X1 (leadership), X2 (motivation), X3 (work environment) have a significant influence on performance (Y).